2007
DOI: 10.1890/1051-0761(2007)017[0091:voceom]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of Climate-Change Effects on Mediterranean Shrublands

Abstract: In general, the socioeconomic analysis of natural systems does not enter into the realms of natural science. This paper, however, estimates the human-welfare effects of possible physicochemical and biological impacts of climate change on Mediterranean shrublands over the coming 50 years. The contingent choice method was applied to elicit the trade-offs in perceived values for three climate-sensitive attributes of shrubland (plant cover, fire risk, and soil erosion) and for the costs of programs designed to mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In addition to the environmental impact, an increase in the area of shrubland affected by erosion is a key concern, for several reasons. An increase of 1 % in the current area of shrubland of the Mediterranean Basin could cause an enormous economic impact (Riera et al 2007).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In addition to the environmental impact, an increase in the area of shrubland affected by erosion is a key concern, for several reasons. An increase of 1 % in the current area of shrubland of the Mediterranean Basin could cause an enormous economic impact (Riera et al 2007).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Kinnell et al (2002), through a CV study, have focused on the willingness to pay (WTP) of hunters for policies to avoid duck population decline in the Prairie Pothole Region due to combined agriculture and global warming pressures in 40 and 100 years. By means of a follow up question to the CE exercise, Riera et al (2007) have asked individuals whether their preferences for policies to avoid CC impacts such as wildfires, soil erosion and shrubland loss occurring in Catalonia over 50 years would have changed if the scenario was 25 or 100 years in the future. All these studies have concluded that individuals are supportive towards very long-term policies benefiting future generations, but they do not distinguish between the different time scenarios considered.…”
Section: Time Sensitivity In the Environmental Valuation Literaturementioning
confidence: 99%
“…Finally an array of studies exists that show fire risk or burnt area reduction as an outcome of broader management policies, aimed at reducing global warming (Riera et al, 2007), increasing the biomass share in energy production (Soliño, 2010;Soliño et al, 2010; or assessing perceived trade-offs between fire prevention and provision of ecosystem services (Mavsar et al, 2013).…”
Section: The Role Of Economic Valuation In Fire Prevention Planningmentioning
confidence: 99%
“…Despite some common design features that can be learnt from these studies with specific consideration of causality aspects some Mediterranean specificities should be considered when designing fire prevention policies such as the broader context of the forest fires issues, the effects of climate change (Riera et al, 2007), the active management of these forest and biomass use possibilities to reduce the incidence of fire (Soliño, 2010;Soliño et al, 2010; or the social perception of forest fire causes and prevention structures (Varela et al 2014a(Varela et al , 2014b.…”
mentioning
confidence: 99%